Criteria of psychological efficiency of realization system of psychology-pedagogical support of sports activity of sportsmen-disables - Boyko G. (Pedagogìka, Psihologìâ ta Mediko-bìologìčnì Problemi Fìzičnogo Vihovannâ ì Sportu, 2010)
Efficiency of the system of psychological pedagogical accompaniment of sporting activity is certain. In research the sportsmen of high qualification took part in sport of invalids. Prevailing high level of readiness of swimmers is rotined to self-realization in competition activity. On results procedure of self-appraisal 68,75 % sportsmen were attained optimum level of readiness, 14,58 % - base (sufficient), 14,58 % - middle (insufficient), 02,08 % - low (critical).